Correction: The X-ray corona in the black-hole binary GRO J1655-40 from the properties of non-harmonically related quasi-periodic oscillations - Rout, Sandeep K. (2023)
This is a correction to ‘The X-ray corona in the black-hole binary GRO J1655–40 from the properties of non-harmonically related quasi-periodic oscillations’ (Rout, Méndez & García 2023). While calculating the rms spectra of the QPOs, the values of the rms amplitude in the 2.06−5.71 keV energy band got inadvertently replaced with the values in the 24.0−29.97 keV energy band. Fig. 1 [which is fig. 3 in Rout et al. (2023)] shows the correct rms spectra in which the fractional rms monotonically increases with energy for both QPOs. This results in a slight improvement in the fit for all three model variants. Table 1 shows the best-fitting parameters for the three model combinations. Since the model was not able to fit the wrong rms values in the original work, the effect of this correction on the results is minimal. The only change worth mentioning is a marginal increase in the size of the vertically elongated corona, although the new and old values are consistent at the 1.5σ−2σ level. Finally, we show the confidence contours of the best-fitting geometrical parameters of the corona for the correct rms spectra in Fig. 2.